Expression of the cathepsin L1 gene of Fasciola hepatica eucaryotic cells - Kuk, Salih; Kaplan, Mustafa; Kalkan, Ahmet; Ozdarendeli, Aykut (My University, 2006)
The parasitic trematode Fasciola hepatica is the causative agent of fasciolosis that is common in ruminants especially sheep and cattle and is occasionally found in humans. Fasciolosis has a worldwide distribution including Turkey and causes major economic losses in agricultural industry. Cathepsin L1 is one of the major molecules in the excretory-secretory products of F. hepatica and is involved in tissue penetration, immune evasion and feeding and therefore may be used in vaccination and serological diagnosis. The aim of this study was to evaluate cloning and expression of the cathepsin L1 gene of F. hepatica eucaryotic cells. For this purpose, total RNA was extracted from adult F. hepatica. Cathepsin L1 DNA amplicons were obtained with the reverse transcription polymerase chain reaction (RT-PCR). The 981 base-coding gene region of cathepsin L1 was amplified using specific primers to the cathepsin L1 gene. Then, the cathepsin L1 gene was cloned into the pCI-neo mammalian expression vector. The presence of the cathepsin L1 gene was confirmed by PCR screening and enzyme digestion assays. So, the resulting recombinant plasmid was named pFhCL1. Afterwards, the pFhCL1 vector was transiently transfected into Vero cells. The presence of the cathepsin L1 proteins was shown by Western immunoblotting.
Fasciola hepatica cathepsin L1 geninin ökaryotik hücrelerde belirlenmesi.
Keywords: Animals; Blotting, Western; Cathepsins; Cercopithecus aethiops; Cloning, Molecular; DNA, Helminth; Fasciola hepatica; Gene Expression Regulation, Enzymologic; Genetic Vectors; Plasmids; Reverse Transcriptase Polymerase Chain Reaction; RNA, Helminth; Transfection; Vero Cells; cathepsin; cathepsin L1, Fasciola hepatica; helminth DNA; helminth RNA; animal; article; biosynthesis; Cercopithecus; enzymology; Fasciola hepatica; gene expression regulation; gene vector; genetic transfection; genetics; isolation and purification; molecular cloning; plasmid; reverse transcription polymerase chain reaction; Vero cell; Western blotting